Keith Tyson. - Bush, Kate; Miller, Jeremy; Delfina, London (London : Delfina London, 1999)
Keith Tyson defines the Artmachine as 'a complex recursive system assembled to generate detailed proposals for artworks'. Delfina will present the first major survey of works by Keith Tyson, including seven large-scale works resulting from the Artmachine and other projects.
Highly ambitious in scale and content, the works in this major exhibition remain resistant to simple categorisation but reveal an extraordinary range of enquiry.
Keith Tyson's project is experimental, prolific and often humourous, but at the same time rigorously challenges the capacity of the artist in a world governed by dynamic electronic systems with seemingly infinite potential.
The Artmachine is able to reference unlimited sources for its proposals, which are then dutifully fabricated by the artist to the best of his abilities without demure to personal style or judgement. The complexity of Keith Tyson's undertaking is evident in the wide scope of the works on display and the extensive leaps in subject matter and form. The machine's proposal for a painting of an English country fair, in paint eighteen inches thick on a spiky armature, has resulted in 'Country Fair with Prize Tent' (1996-99). Resting on hay bails along one wall of the gallery, this 26ft painting, dripping in its thick painterly depiction of rustic life, sits in uneasy proximity to the hi-tech world of 'Dual Workstations, 30 Seconds Late and Early' (1999). In this 'sculpture', two identical work desks are proven, by close observation of the numerous images and graphs pinned to the wall above, to be existing exactly sixty seconds apart. The clock in the photograph, the digital readout on the NASA weather chart, even the seeding of the plants, have been obsessively accomplished within exactly sixty seconds of each other. 'Expanded Photographic Encapsulation' (1999), consists of 101 touch sensitive light units spread across a large area of the floor, each one containing a micro processor wired and connected by word association.
biog., ind. tent., gr. tent. [1 p.], bibliog. [1 p.]
Engels
Keith Tyson, Delfina London, 26.03 - 02.05.1999
Keywords: Tyson, Keith